Polyalphabetic cipher cryptosystem application in making anti-hacker passwords learning management systems in junior high schools - Muhlisatul Mahmudah; Tri Novita Irawati; Friska B. Nur Aini (Alifmatika (Jurnal pendidikan dan pembelajaran Matematika), 2024)
Research on developing an anti-hacker network security system for the learning management system was conducted at SMP Plus Darus Salam. Learning activities at SMP Plus Darus Salam use LMS as a media, which is a program to maximize learning activities at school. its also has risks, it is related to the security of students data work, so network security is needed. Network security used within computer networks to facilitate secure communication in different network entities based on predefined security protocols. On the other hand, the Learning Management System (LMS) is a software platform designed for online educational activities, e-learning programs, and educational resources, simplifying student engagement in learning processes. This study employs applied research methodology, focusing on a single tribune graph, and involves a labeling process for vertices and edges to construct a graph tree, resulting in the generation of ciphertext. This research aims to develop anti-hacker passwords in the SMP Plus Darusalam LMS using a polyalphabetic cipher cryptosystem. The research utilizes a data set comprising 24 LMS account samples. Data collection techniques encompass observation, interviews, distribution of questionnaires, and documentation, while data analysis involves tabulation and the generation of ciphertext codes in the form of usernames and passwords. Based on the results, it shows a total score of 2,096 with an average of 91.13 or a security percentage of 91.13%, which shows that it is successful and useful in the SMP Plus Darus Salam learning management system (LMS) account. Thus, it can be concluded that the secjar (network security) network security efforts made were successful and provided significant benefits in securing learning management system (LMS) accounts at SMP Plus Darus Salam. Therefore, the researcher suggests to the readers to conduct research on the development of anti-hacker network security using Tribun graphs with ???? = 1 and ???? = 2.